Fasting and Diet: Overview in Chronic Lymphocytic Leukemia - Alessandra Trojani; Luca Emanuele Bossi; Roberto Cairoli (Hemato)
Background: This review aims to provide an overview of the potential impact of fasting and diet on cancer, and in particular, on chronic lymphocytic leukemia (CLL), which is the most frequent form of leukemia in the Western world. Methods: Experimental and clinical studies have provided evidence of the crucial role of fasting in enhancing cancer treatment and improving outcomes for oncological patients, particularly at the early stages of the disease. Results: Emerging evidence highlights that fasting creates a differential stress response under critical conditions by fostering the survival of normal cells while limiting the survival and growth of cancer cells. Pivotal studies on CLL have highlighted the potential of fasting and dietary components to influence the stromal microenvironment and certain metabolic pathways, thereby affecting cancer cell apoptosis and immune response. In addition, explorative and initial clinical studies suggest that fasting and specific diets can mitigate the toxicity of chemotherapy. Conclusions: Clinical trials are needed to evaluate the efficacy and safety of nutritional and fasting approaches in cancer and CLL. Future investigations could provide new insights into the potential role of diet and fasting in the prevention and treatment of cancer, potentially leading to more effective and personalized therapeutic strategies.